Pagsasatinig ng pagkabata ang varayti ng wika sa mga premyadong kwentong pambata - Fajilan, Winnielyn F. (Humanities Diliman, 2014)
Writing for children is a way of cultivating their minds. As a special kind of communication, children’s literature entails the use of a language that caters to the needs and skills of the child reader. The study aims to analyse the variety of language used for children in the narratives of eight prize winning children’s stories—awarded the Palanca Award and Philippine Board of Books for Young People (PBBY) prize from 1995-2009—with themes on motherhood or fatherhood. The study found that concepts of motherhood such as that of the traditional homemaker, the OFW, the single mother, and lesbian mothers; concepts of fatherhood like the OFW father, environmentalist and revolutionary parents characterize the selected stories. Through an examination of the dialogues, actions, and descriptions written for the child reader, the paper illustrates how narratives of the self, orality, and intelligence characterize the child protagonist. Hence, an examination of the contemporary children’s stories’ language variety is also an investigation of the prevailing representation of children in Philippine language, literature, and society.